Metabolic requirements of Th17 cells and of B cells: Regulation and defects in health and in inflammatory diseases - Bystrom, Jonas; Taher, Taher E.; Henson, Sian M.; Gould, David J.; Mageed, Rizgar A. (Frontiers in Immunology, 2022)
The immune system protects from infections and cancer through complex cellular networks. For this purpose, immune cells require well-developed mechanisms of energy generation. However, the immune system itself can also cause diseases when defective regulation results in the emergence of autoreactive lymphocytes. Recent studies provide insights into how differential patterns of immune cell responses are associated with selective metabolic pathways. This review will examine the changing metabolic requirements of Th17 cells and of B cells at different stages of their development and activation. Both cells provide protection but can also mediate diseases through the production of autoantibodies and the production of proinflammatory mediators. In health, B cells produce antibodies and cytokines and present antigens to T cells to mount specific immunity. Th17 cells, on the other hand, provide protection against extra cellular pathogens at mucosal surfaces but can also drive chronic inflammation. The latter cells can also promote the differentiation of B cells to plasma cells to produce more autoantibodies. Metabolism-regulated checkpoints at different stages of their development ensure the that self-reactive B cells clones and needless production of interleukin (IL-)17 are limited. The metabolic regulation of the two cell types has some similarities, e.g. the utility of hypoxia induced factor (HIF)1α during low oxygen tension, to prevent autoimmunity and regulate inflammation. There are also clear differences, as Th17 cells only are vulnerable to the lack of certain amino acids. B cells, unlike Th17 cells, are also dependent of mechanistic target of rapamycin 2 (mTORC2) to function. Significant knowledge has recently been gained, particularly on Th17 cells, on how metabolism regulates these cells through influencing their epigenome. Metabolic dysregulation of Th17 cells and B cells can lead to chronic inflammation. Disease associated alterations in the genome can, in addition, cause dysregulation to metabolism and, thereby, result in epigenetic alterations in these cells. Recent studies highlight how pathology can result from the cooperation between the two cell types but only few have so far addressed the key metabolic alterations in such settings. Knowledge of the impact of metabolic dysfunction on chronic inflammation and pathology can reveal novel therapeutic targets to treat such diseases.